2022
DOI: 10.1155/2022/5707953
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Peelu (Salvadora oleoides Decne.): An Unexplored Medicinal Fruit with Minerals, Antioxidants, and Phytochemicals

Abstract: The Peelu (Salvadora oleoides Decne.) fruit is well known for its nutritional and medicinal values. The current study analyzed the chemical composition of Salvadora oleoides fruit. Fresh Peelu fruits were harvested, and physicochemical properties, proximate composition, macro- and micronutrients, and phytochemical properties were determined. Moreover, ethanol and methanol fruit extract was analyzed for physicochemical properties. The Peelu fruit seemed to be a potential source of essential macro- ((nitrogen (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%